Determinants of prices for purebred beef bulls - D.D. Simms; R.P. Jr. Bolze; J. Geske; Kevin C. Dhuyvetter; Ted C. Schroeder (Kansas Agricultural Experiment Station Research Reports, 1997)
Animal characteristics and sale price data for 1651 bulls sold at 26 Kansas purebred beef sales during 1993 were collected and analyzed to determine which factors affected price differentials for beef bulls. Bull sale price varied, from 650 to 20,000 per head. Regression analysis was used to determine the price differential associated with bull traits and marketing factors. Black bulls in the Simmental, Gelbvieh, and Limousin breeds brought premium s of 15% to 53% compared to their nonblack peers. Conformation, disposition , and muscling affected sell prices. Bulls with lower birth weights and birth weight expected progeny differences (EPD) brought higher prices. Bulls with higher adjusted weaning weights, weaning weight EPD, and milk EPD also brought higher prices, although these varied depending upon bull breed. Several marketing factors, including sale order, semen retention, and pictures in the sale catalogs, influenced bull prices. Bull buyers can use this information to make more informed bull buying decisions, and purebred producers can use results to target production and marketing.
Keywords: Cattlemen& #x27; s Day; 1997; Kansas Agricultural Experiment Station contribution; no. 97-309-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 783; Beef; Bull prices; Bull EPD; Bull marketing